A Case Study on the Utility of Sustained Evaluation Practice in Public Health Partnership - Ayana N. Perkins PhD (SAGE Publishing, 2018)
This article explores a case study of the potential influence of a capacity building investment toward public health partnerships (PHPs) targeting asthma. This case study explores what factors were salient among PHPs who were indirect recipients of a funder's capacity building. Our case study suggests that a funder's capacity building efforts may be linked to evaluation practice guidelines and decisions toward individual and organizational level use of evaluation use within partnerships. Moreover, examining the contextual factors that were associated with the evaluation of these PHPs explicates where adjustments may be needed in applying capacity building to the PHP setting. This case study has implications for future health planning policies.